KONDISI PSIKOLOGIS SISWA YANG BROKEN HOME DI SMP NEGERI 40 PEKANBARU - Sari, Fani Novita; Saam, Zulfan; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Psychological condition of broken home student that is a state of psychic or soul that experiencing shock caused by family condition which fall apart because of parent no longer care about situation and family at home like parents do not concern to their children, either problem at home, school until on the social development of his children in the community. Where a child who comes from a harmonious family then the psychological condition is good and children who come from broken home family then the psychological condition is disrupted. The role of the family in the development of the child's pediatric condition is very important. This study aims to determine the psychological condition of broken home students at SMP Negeri 40 Pekanbaru. The psiological condition indicator of broken student home include emotion, moral and mental. The method used in this research is quantitative descriptive research. Based on the results of research from the subject of 43 students SMP Negeri 40 Pekanbaru is in the medium category is 83.72%, as for the behavior they do is easy to forgive those who hurt them, able to get out of their sadness experienced, trying to forgive friends who interfere with them , doing duties with full responsibility, parents pay attention to the association of their children and they feel happy with life.Keyword : Psychological Condition, Broken Home